2021
DOI: 10.1519/jsc.0000000000002951
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Competitive Soccer Match on Jump Performance and Interlimb Asymmetries in Elite Academy Soccer Players

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(75 citation statements)
references
References 44 publications
6
66
3
Order By: Relevance
“…By comparing the magnitude of inter-limb asymmetry between the rested and fatigued state for each test, we found that the asymmetry increased post fatigue in triple-hop distance. Most of previous studies have reported similar ndings: the inter-limb asymmetry in unilateral CMJ height increased post fatigue among active male adults (aged 28.9 ± 5.1 years) [9] and elite adolescent male soccer athletes (aged 17.6 ± 0.5 years) [15]; the inter-limb asymmetry in peak force, peak power, and mean power during the unilateral CMJ increased post fatigue among male Judo athletes (aged 22.5 ± 3.6 years) [16]. Collectively, these ndings indicate that fatigue ampli es the inter-limb asymmetry in leg power, suggesting the necessity of assessing the inter-limb asymmetry at both the nonfatigued and fatigued state.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…By comparing the magnitude of inter-limb asymmetry between the rested and fatigued state for each test, we found that the asymmetry increased post fatigue in triple-hop distance. Most of previous studies have reported similar ndings: the inter-limb asymmetry in unilateral CMJ height increased post fatigue among active male adults (aged 28.9 ± 5.1 years) [9] and elite adolescent male soccer athletes (aged 17.6 ± 0.5 years) [15]; the inter-limb asymmetry in peak force, peak power, and mean power during the unilateral CMJ increased post fatigue among male Judo athletes (aged 22.5 ± 3.6 years) [16]. Collectively, these ndings indicate that fatigue ampli es the inter-limb asymmetry in leg power, suggesting the necessity of assessing the inter-limb asymmetry at both the nonfatigued and fatigued state.…”
Section: Discussionsupporting
confidence: 61%
“…The unilateral jump testing has been widely used to assess the interlimb asymmetry in lower-limb power as the single-leg jumping movement is common in sports and the assessment is time-e cient [9]. Previous ndings showed that the inter-limb asymmetry in single-leg countermovement jump (CMJ) performance increased post fatigue among adolescents and adults [9,15,16]. In addition to the unilateral jump performance, the Star Excursion Balance Test (SEBT) and its modi ed version (Y Balance Test) have been widely used to examine inter-limb asymmetry in dynamic balance and neuromuscular control.…”
Section: Introductionmentioning
confidence: 99%
“…The studies used different designs. A differentiation can be made between studies regarding inter-limb asymmetries during a loading protocol [20,21,[30][31][32][33][34] (Table 3) and studies regarding inter-limb asymmetries with a supplementary task in a pre-post design [7,16,[35][36][37][38] (Table 4). In six studies, the subjects were tested for asymmetries at different points of time during the loading protocol [20,21,[31][32][33][34].…”
Section: Methodsmentioning
confidence: 99%
“…In six studies, the subjects were tested for asymmetries at different points of time during the loading protocol [20,21,[31][32][33][34]. One study interspersed the loading protocol with several single-leg countermovement jumps (SLCMJ) to test asymmetries [30], and six studies used other tasks/procedures, such as jumps, isokinetic strength testing or a gait analysis, to test the subjects before and after the loading protocol [7,16,[35][36][37][38]. Furthermore, all studies investigated the acute influence of exercise-induced fatigue on inter-limb asymmetries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation